2019
DOI: 10.1111/head.13716
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Migraine on Driving: Current Understanding, Future Directions, and Potential Implications of Findings

Abstract: Objective.-To review the published findings relevant to migraine and driving performance, with an intent to encourage discussion on research which may broaden understanding in this area and help educate healthcare providers and their patients. Background.-Motor vehicle crashes result in more than 35,000 deaths and more than 2 million injuries annually in the United States. Migraine is one of the most prevalent diseases in the world, and many symptoms associated with migraine attacks have the potential to negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
8
1
Order By: Relevance
“…Our findings also show an association between migraine/tension headache and increased likelihood of accidents, although no comparable studies have been found that indicate such an association. Migraine alone has also been associated with fatigue and drowsiness, and driving performance [28]. The incidence of migraine among seamen in the study was rather high (18.4%), but due to a lack of reports on seamen and their physical health, a comparison is difficult.…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…Our findings also show an association between migraine/tension headache and increased likelihood of accidents, although no comparable studies have been found that indicate such an association. Migraine alone has also been associated with fatigue and drowsiness, and driving performance [28]. The incidence of migraine among seamen in the study was rather high (18.4%), but due to a lack of reports on seamen and their physical health, a comparison is difficult.…”
Section: Plos Onementioning
confidence: 77%
“…Studies from Iceland and other countries indicate that seamen often feel that they are tired [24], and their sleep is often disrupted, due to both noise and the movements of the vessel [26]. Inadequate sleep increases the likelihood of headache and can also be a cause of headache [27,28]. Various environmental factors at sea are believed to have a negative impact on seamen´s health.…”
Section: Introductionmentioning
confidence: 99%
“…Malone et al [88] CB1 receptor activation in the vIPAG attenuated trigernirucervical complex activity. This effect was inhibited by the addition of the CB1 receptor antagonist or the 5HT1B/1D receptor antagonist.…”
Section: Follow-upmentioning
confidence: 99%
“…4 Migraine symptoms have the potential to adversely affect driving safety. 5 Prospective studies in New Zealand and Canada reported significantly increased risks of motor vehicle crash (MVC) injuries in people with prevalent (i.e., ever diagnosed or treated) migraine, while a smaller retrospective study in male military drivers found migraine diagnosis associated with police-reported MVCs. [6][7][8] Migraines could also reduce crash risk if symptoms lead to reductions in driving.…”
Section: Introductionmentioning
confidence: 99%
“…9 Medications to prevent or treat migraine, including triptans, opioids, barbiturates and antiemetics for acute attacks, or β-blockers, antidepressants, or antiepileptics used as preventive treatments, may reduce driving safety. 5 However, by decreasing migraine symptoms, such medications might also reduce impaired driving and promote safety. Vingilis et al (2012) simultaneously examined migraines and pain medications (not necessarily prescribed specifically for migraine) and found that the increased odds of MVC…”
Section: Introductionmentioning
confidence: 99%